Women's Health and Biomechanics Where Medicine and Engineering Meet (Lecture Notes in Computational Vision and Biomechanics,, 2018)
This book focuses on particular mental and physical aspects of women's health, presenting topics concerning the pelvis and pelvic floor dysfunction and the breast during a woman's life, such as rehabilitation for pelvic and breast disorders, and the benefits of biomechanical analysis in treating these conditions. With each chapter providing a brief survey of a major research area related to the theme, the book offers an integrated overview of topics such as the bio-psycho-social model of women's health, pelvic floor evaluation in sports, the breast, pregnancy and delivery. It is a valuable resource for a wide range of readers, including researchers, graduates and professionals. .